Lycopene protects against myocardial ischemia-reperfusion injury by inhibiting mitochondrial permeability transition pore opening - Li X; Jia P; Huang Z; Liu S; Miao J; Guo Y; Wu N; Jia D (Dove Medical Press, 2019)
Xuying Li,1,* Pengyu Jia,1,* Zijun Huang,1 Shuang Liu,1 Jiaxin Miao,1 Yuxuan Guo,1 Nan Wu,2 Dalin Jia11Department of Cardiology; 2The Central Laboratory, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning 110001, People’s Republic of China*These authors contributed equally to this workBackground: Mitochondria permeability transition pore (MPTP) is an important therapeutic target for myocardial ischemia-reperfusion injury (MIRI). Lycopene (LP) is a potent antioxidant extracted from the mature fruits of plants and has been reported to protect against MIRI; however, its mechanism of action has yet to be completely elucidated. The present study aimed to investigate the role of MPTP in the cardioprotection of LP.Methods: H9c2 cells were pretreated with LP for 12 hrs and were subjected to 12-hr hypoxia/1-hr re-oxygenation, and cell viability was measured by a Cell Counting Kit-8 (CCK-8) assay. Male rats were subsequently intraperitoneally injected with LP for 5 consecutive days. At 24 hrs following the final injection, the rat hearts were isolated and subjected to 30-min ischemia/120-min reperfusion using Langendorff apparatus. The myocardial infarct size was measured by a TTC stain. Opening of the MPTP was induced by CaCl2 and measured by colorimetry. The change in mitochondrial transmembrane potential (ΔΨm) was observed under a fluorescence microscope. Apoptosis was measured by flow cytometry and a TUNEL stain, and the expression of apoptosis-related proteins was detected by Western blotting.Results: LP pretreatment significantly increased cell viability, reduced myocardial infarct size and decreased the apoptosis rate. In addition, opening and the decrease of ΔΨm were attenuated by LP and the expressions of cytochrome c, APAF-1, cleaved caspase-9 and cleaved caspase-3 were also decreased by LP. However, these beneficial effects on MIRI were abrogated by the MPTP opener (atractyloside). Furthermore, LP treatment markedly increased Bcl-2 expression, decreased Bax expression and the Bax/Bcl-2 ratio.Conclusion: The results of the present study demonstrated that LP protects against MIRI by inhibiting MPTP opening, partly through the modulation of Bax and Bcl-2.Keywords: myocardial ischemia reperfusion injury, lycopene, mitochondrial permeability transition pore, apoptosis